Poverty within economy. A controversial discussion on social and hospital attention in the 16th c. - Mariano Monge Juárez; Cristina López Osuna (Universidad de Alicante, 1998)
The present article is a reflection on the opposition of the two main ways of understanding social and hospital care during the 16th century. On the one hand, there were those who argued that caring it should be a sort of religious charity. On the other hand, there were the humanists who stood for social reforms and education for marginalized sectors. The hypothesis presented in this article comes from the following consideration: «Whenever there is a development of capitalist performance, poverty begins to be a threat to the state, thus power oligarchies are obliged to build a policy of sanitary care opposite to the care offered by the Church who traditionally has had the control of the hospitals». The debate about the theoretical concept of the social-hospital-care, started during the 16th century surfaces today in the form of the welfare crisis. At present we face a new controversial debate on who should deal with the administration of hospital care; either the government or the private sector.